Analisis Framing Berita Kecemasan Masyarakat Penularan Covid 19 Pada Detik.Com - Moch Hasan; Ratna Puspita Sari (DIGICOM : Jurnal Komunikasi dan Media, 2023)
One of the news that is developing at this time is the news of Covid-19 where the news is always raised every day. Each media is different in packaging the news, it is influenced by ideology and media owners as seen from the news framing done to the media. This study uses a constructionist paradigm with a qualitative approach. The main source used for this research is news about Covid-19 in the online media DetikNews.com. The results show that Modigliani and Gamson's framing analysis of the Covid-19 news in the online media detik.com shows that in March the Covid-19 pandemic was very stressful, worrying, and full of vigilance due to this new disease. very dangerous and can cause death. However, as time went on, people began to ignore the spread of this corona virus, many regulations were violated because it was getting boring with this kind of situation. Like doing activities at home, and not only that, the government is not transparent to the media, so the public does not know detailed information about cases of Covid-19 patients, so that trust in the existence of Covid-19 will continue to fade. And, coupled with the media always highlighting or displaying state finances in the form of social assistance, causing some not to be channeled properly, so that Covid-19 becomes a business and political field for those in power.